Development of Methylmercury Analysis by Ultra-High Performance Liquid Chromatography Coupled with ICP-MS and Its Application on Sharks’ Meat Measurement - Satriyo Krido Wahono; Dwi Siswanta; Nurul Hidayat Aprilita; Suratno Suratno (Indonesian Journal of Chemistry, 2023)
This study analyzed MeHg in a fast, simple, low-waste, and accurate by using ultra-high liquid chromatography coupled with inductively coupled plasma mass spectrometry. Simple preparation by liquid extraction with sonication at room temperature was effective extract MeHg from Certified Reference Material (CRM) and shark meat samples. Effective MeHg separation was achieved in less than 300 s using a C18 Hypersil Gold analytical column with a mobile gradient phase of 0.5% (w/v) L-cysteine in 2% (v/v) HNO3 and 100% methanol. The MeHg was extracted from 100 mg of shark meat using 1 mL of 0.5% (w/v) L-cysteine in 2% (v/v) HNO3 and sonicated for 30 min. Analysis of certified reference material (DORM-4) showed values between the experimental and certified values. The observed limit of detection and quantification MeHg were 0.86 and 2.85 pg/L, respectively. This method was applied to measure MeHg in shark meat from Binuangeun areas. The MeHg concentration in Rhizoprionodon acutus was 0.22–0.63 mg/kg wet weight (w.w.), Squalus hemipinis 0.68–1.14 mg/kg w.w., and 0.29–1.22 mg/kg w.w. for Sphyrna lewini. This study provides a quick and easy method to evaluate MeHg in shark meat or other seafood products and applies to many samples in a single assay.